SUITABILITY OF WATERS FOR SNORKELING TOURISM ON TERNATE ISLAND, NORTHWEST ALOR SUB-DISTRICT, ALOR DISTRICT - Imanuel Lamma Wabang; Paulus Edison Plaimo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Ternate Island, Alor Regency is an area that has the potential for diving and snorkeling tourism, so it is necessary to study the suitability and carrying capacity of the area. This study aims to determine the potential of coral reef ecosystems and the level of suitability for snorkeling tourism. The method used is the LIT method based on equations (English et al. 1994). The results of the study for snorkeling tours show that there are three suitable stations (S2), namely stations 1, 2, and 3, while station 4 is not in the appropriate category (S3). The carrying capacity of the area for snorkeling tours is obtained by an area of ± 110,915 m2 with a total of 443 people/day with a carrying capacity of ± 44 people/day